Fertigation of ‘BRS Princesa’ banana with humic substance and saponin-based plant extracts - de Melo, Diego Magalhães; Coelho, Eugênio Ferreira; Rosa, Raul Castro Carriello; Borges, Ana Lúcia; dos Santos, Djalma Barbosa; Pereira, Bruno Laecio da Silva (Revista Ceres, 2017)
The use of humic substances and plant extract has been increasing mainly in organic crop systems without scientificbased recommendations. Research is necessary to evaluate the feasibility and the recommendations of these substances. The objective of this work was to evaluate the effect of humic substances (humic and fulvic acids) applied by fertigation with and without saponin-based plant extracts on growth and yield of ‘BRS Princesa’ banana. The experiment was carried out using the banana cultivar ‘BRS Princesa’, at a spacing of 2.0 × 2.5 m, fertigated by drip irrigation in a Dystric Densic Xantic Ferralsol, at the Recôncavo da Bahia, Brazil. Treatments consisted of five doses of humic substances (0.0; 70; 105; 140, and 210 L ha-1 cycle-1) applied with and without a saponin-based plant extract in a randomized block design in split-plot scheme. The following growth variables were evaluated: number of leaves, pseudostem height, pseudostem diameter, and length and width of the third leaf. The number of fruits/hand and hands/bunch, hand and bunch yield, and length and fruit diameter of the second central hand were evaluated during harvest. The doses of humic substances influenced only pseudostem height. Hand yield, as well as fruit length and diameter of ‘BRS Princesa’ banana were higher in plants fertigated with humic substance and plant extract in comparison with plants fertigated with only humic substance.